Empowering Nurses, Midwives and Allied Health Professionals to Gain an Academic, Research and Quality Improvement Experience within Clinical Practice - Bell, Cate Ann; Colleran, Vivienne (International Journal of Practice-based Learning in Health and Social Care, 2019)
The NHS Multi-Professional Framework for Advanced Clinical Practice in England (Health Education England, 2017) sets out an expectation that all health and care professionals working at advanced clinical practice (ACP) level demonstrate a range of standard clinical academic capabilities across four pillars: clinical practice, leadership and management, education, and research. To achieve this, practitioners and employers need to work collaboratively to develop these capabilities and recognise how they contribute to improving the quality of care. However, the culture, leadership values and infrastructure of clinical practice environments limit opportunities for such clinical academic development (van Oostveen et al., 2017), resulting in a strong clinical bias amongst advanced practitioners with limited focus on research and leadership. To address this, we propose Nursing, Midwifery and Allied Health Professional (NMAHP) groups require specific development programmes that combine an academic, research and quality improvement experience grounded within clinical practice roles. In this article, we describe Western Sussex Hospitals NHS Foundation Trust Clinical Improvement Scholarship (CIS), a twelve-month programme combining work on a practice-based quality improvement project alongside education for leadership, research and quality improvement. Early indicators from the first and second cohorts suggest a significant increase in research and leadership knowledge with ‘scholars’ reporting increased commitment and confidence in utilising research evidence to improve care. Line managers also suggest a notable rise in professional confidence in the delivery of care and organisational competency. We therefore conclude that the CIS programme has impacted positively on professional capabilities and clinical quality within the Trust.